Asprosin-induced alterations in female rat puberty and reproductive hormonal profiles - Kacar, Emine; Oz, Zeynep Dila; Serhatlioglu, Ihsan; Tektemur, Nalan Kaya; Ozdede, Mehmet Ridvan; Yalcin, Tugce; Kelestimur, Haluk (Taylor & Francis Ltd, 2025)
ObjectiveTo investigate the comprehensive effects of daily chronic asprosin administration on various pubertal and reproductive parameters in female rats. This study aims to elucidate the role of asprosin in regulating the onset of puberty and its influence on hormonal profiles and ovarian histology.MethodsAsprosin was administered intraperitoneally (i.p.) at a dose of 500 ng/kg daily for eight weeks. Hormonal assays and histological analyses were performed to evaluate the effects of asprosin on the onset of puberty and reproductive function.ResultsDaily chronic administration of asprosin accelerated the onset of the first oestrus. Hormonal assays revealed significant elevations in serum levels of Follicle-Stimulating Hormone (FSH) and Oestradiol (E2), while Inhibin B levels decreased. Histological evaluations demonstrated an increased number of primary and secondary follicles in ovarian tissue, without affecting primordial follicle counts or reproductive organ weights.ConclusionsRole of adipokines in regulating puberty and reproductive function has increasingly gained recognition. This study aimed to provide the first comprehensive examination of the effects of daily chronic asprosin administration on pubertal and reproductive parameters in female rats. Utilising hormonal assays and histological analyses, asprosin was administered intraperitoneally (i.p.) at a dose of 500 ng/kg, daily, for eight weeks. Our findings revealed that daily chronic administration of asprosin accelerated the onset of the first oestrus. Hormonal assays showed significant elevations in serum levels of Follicle-Stimulating Hormone (FSH) and Oestradiol (E2), while Inhibin B levels decreased. Histological evaluations demonstrated an increased number of primary and secondary follicles in ovarian tissue, without affecting primordial follicle counts or reproductive organ weights. These results provide new insights into asprosin's role in advancing the age of first oestrus and modulating hormonal profiles, thereby offering potential benefits to the female reproductive system.
Keywords: Asprosin; female rat; fertility; puberty; reproduction